Demonstration of a clinical case based on the phenotypic approach of rosacea therapy - Marianna B. Drozhdina; Varvara A. Bobro (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
Rosacea is a chronic inflammatory disease of the skin mainly of the central facial region, having gender and age correlations. Currently, more and more data is accumulating on the analysis of rosacea phenotypes, scientific discussions are underway on the feasibility of switching from subtype classification to phenotypic classification to justify individualized approaches to therapy. The phenotypic classification is based on the manifestations of rosacea and distinguishes diagnostic signs from the main and secondary symptoms. Thus, phymatous changes and persistent central facial erythema are the only diagnostic signs (criteria) of rosacea, and erythema, telangiectasia and inflammatory papules/pustules are the main symptoms and only in combination can indicate the diagnosis of rosacea. Secondary signs of rosacea are hot flashes, burning, pain, swelling and a feeling of dryness. The symptoms of rosacea are based on various pathophysiological mechanisms, so therapy in most cases will consist of a combination of topical agents with systemic drugs or physiotherapy. The article presents a clinical case of rosacea based on a phenotypic approach to therapy.